DEVELOPMENT OF CASH WAQF BENEFITS SYNERGY FOUNDATION IN THE ECONOMIC EMPOWERMENT OF THE UMMAT - Mamat Rachmat Effendi (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
This paper discusses the development of cash waqf benefits which is directed at empowering the community's economy carried out by the synergy foundation in West Java. Cash waqf as one of the shari'ah financial instruments should be able to provide added value usefulness and a multifier effect in reviving the community's economy. The aim is to map the quality of institutions in managing the benefits of cash waqf for the economic empowerment of the people. The approach used is case studies with qualitative methods, the data were analyzed descriptively with a phenomenological naturalistic paradigm which emphasizes the nature of social reality and studies what appears in society. The results obtained in the field Sinergi Foundation have carried out professional, transparent and accountable, financial management using the accounting standard for zakat PSAK 109. The financial reports are audited by an independent public accountant and the results are Unqualified (WTP).